The Role of Hydrogeological Monitoring in a Multidisciplinary Context for the Preservation of the Critical Zone in the Natural Reserve of Castelporziano Estate - Sbarbati, Chiara; Lacchini, Alessandro; Petitta, Marco (Frontiers in Earth Science, 2022)
In the last years the Critical Zone (CZ) science quickly developed involving different disciplines, depending on the specific research focus. This multidisciplinary approach highlights the relevance of the Underground component of the Critical Zone (UCZ) in regulating water cycle, which can influence the complex equilibrium of the whole CZ. In this study we deeply analyze the evolution during time of different parameters characterizing the saturated and unsaturated parts of UCZ of the Castelporziano Estate, a natural reserve located in a coastal area, close to the Rome. The purposes of these activities are to monitor the potential depletion of groundwater resources and to understand the recharge mechanism processes characterizing the aquifer in the framework of occurring climate changes, net of anthropogenic pressure. The long-term analyses of water table variations, carried out for the last 25 years, allowed to preliminarily identify four different ranges of slope coefficient of the water table, characterizing different areas of the Estate. Specifically, the Northern, the Central and Coastal areas shown a general depletion trend in piezometric levels, while in Eastern area a positive trend has been recognized. An additional long-term analysis of piezometric level variations allowed to confirm the presence of the four recharge areas and the comparison between annual recharge and water table levels assessed the relationship between saturated UCZ and meteoric recharge in the identified areas. To evaluate the role of unsaturated UCZ in recharge mechanisms, the water content in the first meter of soil has been also analyzed, showing different responses of outcropping sediments in capturing rainfall during different period of the year and under different rainfall input conditions, highlighting the pivotal role of rainfall for the Castelporziano UCZ, both for deep recharge of the water table and for the feeding the forest roots. Stable isotopes confirm that Castelporziano UCZ feeding is strongly dependent to local meteoric recharge, highlighting also that evaporation processes are active in limited. The obtained results assess that the monitoring of UCZ has a crucial role for the correct preservation of the more complex environmental system which includes groundwater resources and coastal Mediterranean forest.